Application of Mandarin language module for improving language speaking skills - Putu Prinda D`amour Nisa (English, 2019)
The Chinese language is very different from the Indonesian language. The writing and pronunciation of this language is quite complicated because this language uses the script called hànzì and the pronunciation is called pīnyīn. Pīnyīn is a Latin syllable which has tone in their syllable. Based on observations at the Dwijendra Vocational School in Denpasar, researchers still found many problems in Chinese learning activities. One of the problems lies in the teaching materials used. There is no handle teaching materials accordance the curriculum. The next problem lies in students' speaking skills. Therefore, the researchers tried to use a Chinese module that was made by themselves to improve students' speaking skills. Using Classroom Action Research (CAR) as the basis for research can be seen the influence of this Chinese module on the development of student learning achievement. Pre-Test Testing, Cycle 1 Test and Cycle 2 Test use the same test questions by testing 30 vocabulary words that are run orally by students. In the pre-test 21 students (95%) were ranked D and only 1 student (5%) was ranked C. The percentage of each indirect cycle increased until the final result of cycle 2 was 27% of students still ranked D, 50% of students rated C and 23% of students are rated B. This result is quite satisfying for researchers because Chinese language skills are quite difficult lessons for beginners especially those who have very little study time but they are must have a lot of pronunciation and vocabulary.